Dick Whittington - Fremont, Isabelle (University Press Plc, 1992)
Many years ago, there was a boy called Dick Whittington. He lived in a small village a long way from London.Dick's father and mother were dead. He had no home and no one looked after him, so he was often hungry. He had no house to live in, and he often slept in the fields or under the trees...
Keywords: Juvenile Fiction / Adventure